Kajian Naratif: Kesehatan Kardiovaskuler pada Masa Menopause: Narative Review: Cardiovascular Health During Menopause - Jatmiko Susilo; Sari, Kartika; Rini Susanti; Siti Haryani; Ana Puji Astuti (Universitas Ngudi waluyo, 2024)
Menopause (MP) is associated with a significant increase in blood pressure, body mass index (BMI), obesity, and body fat distribution. At this time, women have a higher risk of cardiovascular disease (PKV) than men according to their age due to reduced levels of endogenous estrogen. This article aims to examine the role of estrogen during MP in relation to the risk of cardiovascular disorders and estrogen replacement therapy. Articles were obtained from PubMed, and ScienceDirect articles, using the keywords “estrogen and MP”; “estrogen and lipid metabolism”, “estrogen and cardiovascular”, and “menopausal hormone therapy”. The final set includes 82 academic articles published from 1998-2024. Estrogens produce increased lipid metabolism, have effects on biomarkers of vascular activity by activating vasodilator pathways and inhibiting vasoconstrictor pathways mediated by the sympathetic nervous system and angiotensin. Estrogen plays an important role in regulating the cardiovascular system. From the perspective of oxidative stress provides a strategy for the treatment of cardiovascular disease in postmenopausal women. Abstrak Menopause (MP) dikaitkan dengan peningkatan signifikan tekanan darah, indeks massa tubuh (IMB), obesitas, dan distribusi lemak tubuh, pada masa ini perempuan memiliki resiko penyakit kardiovaskuler (PKV) lebih tinggi dibanding laki-laki sesuai usianya akibat berkurangnya kadar estrogen endogen. Artikel ini bertujuan untuk mengkaji peran estrogen pada masa MP dalam hubungannya dengan resiko gangguan kardiovaskuler serta terapi sulih estrogen. Artikkel-artikel diperoleh dari PubMed, dan ScienceDirect, menggunakan kata kunci “estrogen dan MP”; “estrogen dan metabolism lipid”, “estrogen dan kardiovaskuler”, “terapi hormon MP”. Set terakhir mencakup 82 artikel akademis tahun terbit 1998-2024. Estrogen meningkatkan metabolisme lipid, memiliiki efek pada biomarker aktivitas pembuluh darah dengan mengaktivasi jalur vasodilator dan menghambat jalur vasokonstriktor yang dimediasi oleh sistem saraf simpatis dan angiotensin. Estrogen berperan penting dalam pengaturan sistem kardiovaskuler. Dari perspektif stres oksidatif memberikan strategi untuk pengobatan penyakit kardiovaskular pada wanita MP.